Роль самостоятельной работы студентов в профессиональном образовании - Орел-Халик, Ю. В.; Orel-Khalik, Y. V.; Орел-Халік, Юлія Владиславівна (Минск : БГУ, 2021)
В современном профессиональном образовании изменились тенденции от простого, пассивного получения знаний к формированию навыков и умений саморазвития и самообучения. Это означает, что большинство учебного времени студенты проводят самостоятельно, работая вне аудитории. В статье раскрыта сущность понятия «само- стоятельная работа студентов». In higher medical education, the focus has changed from the simple gaining of knowledge to learning objectives and skills. This means that, the majority of students’ learning time is spent independently working outside the classroom. Students must take an active part in making their own decisions how to achieve knowledge, and how to plan individual study time. The article reveals the essence of the concept of «self-study activity of students».
Role of students‘ self-study activity in the professional training
Keywords: самостоятельная работа студентов; электронные ресурсы; рабочая программа; учебная дисциплина; комплексный подход; students‘self-study activity; digital resources; educational program; integrated approach